2015
DOI: 10.1111/obr.12239
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and vitamin D deficiency: a systematic review and meta‐analysis

Abstract: Over the past decade, there have been an increasing number of studies on the association between vitamin D deficiency and anthropometric state. However, we did not identify any meta-analyses of the relationship between obesity and vitamin D deficiency in different age groups. Thus, we evaluated the association between obesity and vitamin D deficiency. We searched for observational studies published up to April 2014 in PubMed/Medline, Web of Science and Scopus databases. We performed a meta-analysis in accordan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
483
6
43

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 717 publications
(560 citation statements)
references
References 49 publications
28
483
6
43
Order By: Relevance
“…High waist circumference was observed in the Vitamin D Deficiency group, which can be attributed to the active role that vitamin D plays in the adipose tissue by modulating the inflammatory response and reducing adipogenesis and adipocyte secretion [39]. A meta-analysis including groups of different ages found an association between vitamin D deficiency and obesity, regardless of age, latitude, cutoff point for vitamin deficiency, and the Human Development Index of the region where the study was carried out [40].…”
Section: Discussionmentioning
confidence: 99%
“…High waist circumference was observed in the Vitamin D Deficiency group, which can be attributed to the active role that vitamin D plays in the adipose tissue by modulating the inflammatory response and reducing adipogenesis and adipocyte secretion [39]. A meta-analysis including groups of different ages found an association between vitamin D deficiency and obesity, regardless of age, latitude, cutoff point for vitamin deficiency, and the Human Development Index of the region where the study was carried out [40].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, both calcium and vitamin D absorption are diminished with aging leading to their lower serum concentration (Gallagher 2013). There is a strong relationship between low calcidiol concentrations and increasing levels of obesity (Pereira-Santos et al 2015). It has been shown that even when controlling for sunlight exposure, obese individuals are significantly more likely to have lower calcidiol concentration, indicating inadequate vitamin D status , Pereira-Santos et al 2015.…”
Section: Calcitriol As a Mediator For All Three Tissuesmentioning
confidence: 99%
“…Indeed, serum 25(OH)D is consistently lower in obese than lean individuals (94) . A recent meta-analysis found that prevalence of VD deficiency was 35 % higher in obese and 25 % higher in overweight compared with lean subjects (95) . In addition, 25(OH)D plasma levels are inversely correlated to all the parameters of obesity, including BMI, fat mass and waist circumference (96,97) , and increased dietary intake of VD, resulting in higher 25(OH)D plasma levels, is associated with a lower visceral adiposity (98) .…”
Section: Effects Of Vitamin D On Obesity and Associated Disorders Inmentioning
confidence: 99%